A Comparison of Facial Landmark Detection Methods - (:unkn) unknown (IEEE, 2018)
Face analysis is a rapidly developing research area and facial landmark detection is one of the pre-processing steps. In recent years, many algorithms and comprehensive survey/challenge papers have been published on facial landmark detection. In this work, we analysed six survey/challenge papers and observed that among open source systems deep learning (TCDCN, DCR) and regression based (CFSS) methods show superior performance.
Keywords: face analysis; facial landmarks; FACE ALIGNMENT